DREAM users manual: a tool for evaluating the effects of agricultural R&D - Wood, Stanley; You, Liangzhi (International Food Policy Research Institute, 2001)
DREAM, or Dynamic Research Evaluation for Management, is a menu-driven software package for evaluating the economic impacts of agricultural research and development (R&D). Users can simulate a range of market, technology adoption, research spillover, and trade policy scenarios based on a flexible, multi-market, partial equilibrium model.